The disordered N-terminus of HDAC6 is a microtubule-binding domain critical for efficient tubulin deacetylation - Ustinova, Kseniya; Novakova, Zora; Saito, Makoto; Meleshin, Marat; Mikesova, Jana; Kutil, Zsofia; Baranova, Petra; Havlinova, Barbora; Schutkowski, Mike; Matthias, Patrick; Barinka, Cyril (The Journal of biological chemistry, 2020)
Histone deacetylase 6 (HDAC6) is a multidomain cytosolic enzyme having tubulin deacetylase activity that has been unequivocally assigned to the second of the tandem catalytic domains. However, virtually no information exists on the contribution of other HDAC6 domains on tubulin recognition. Here, using recombinant protein expression, site-directed mutagenesis, fluorimetric and biochemical assays, microscale thermophoresis, and total internal reflection fluorescence microscopy, we identified the N-terminal, disordered region of HDAC6 as a microtubule-binding domain and functionally characterized it to the single-molecule level. We show that the microtubule-binding motif spans two positively charged patches comprising residues Lys-32 to Lys-58. We found that HDAC6-microtubule interactions are entirely independent of the catalytic domains and are mediated by ionic interactions with the negatively charged microtubule surface. Importantly, a crosstalk between the microtubule-binding domain and the deacetylase domain was critical for recognition and efficient deacetylation of free tubulin dimers both in vitro and in vivo Overall, our results reveal that recognition of substrates by HDAC6 is more complex than previously appreciated and that domains outside the tandem catalytic core are essential for proficient substrate deacetylation.
Keywords: protein motif; Catalytic Domain; Histone Deacetylase 6; Humans; histondeacetylasa 6; Substrate Specificity; protein-protein interaction; Protein Binding; Acetylation; total internal reflection fluorescence (TIRF); acetylace; Tubulin; cytoskeleton; Microtubules; lidé; proteinové domény; intrinsically disordered protein; structure-function; substrate specificity; microtubule-associated protein (MAP); mikrotubuly; Amino Acid Sequence; histone deacetylase 6 (HDAC6); substrátová specifita; katalytická doména; vazba proteinů; tubulin; Protein Domains; post-translational modification; sekvence aminokyselin